Clinical characteristics and genetic analysis of gene mutations in a Chinese pedigree with Peutz‐Jeghers syndrome. Issue 4 (3rd March 2019) - Qiu, Yudian; Xuan, Tao; Yin, Mujun; Gao, Zhidong; Guo, Peng; Chen, Xi; Ye, Yingjiang; Shen, Zhanlong
Key Clinical Message: The genome‐wide sequencing information of PJS is still lacking. Our result demonstrates that c.862+2T>C variant on STK11 as an important foundation of molecular mechanism in this familial PJS. Variants in KDR and MLL3 may play important roles in the initiation and development of this familial PJS polyps. Abstract : The genome‐wide sequencing information of PJS is still lacking. Our result demonstrates that c.862+2T>C variant on STK11 as an important foundation of molecular mechanism in this familial PJS. Variants in KDR and MLL3 may play important roles in the initiation and development of this familial PJS polyps.